(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Systemic lupus erythematosus (SLE) is a multi-system autoimmune disease where chronic gingivitis and periodontitis often serve as early clinical markers. Despite their prevalence, dental literature remains divided on whether SLE leads to long-term tissue preservation or rapid necrotic destruction and premature tooth loss. This study aims to enhance the diagnostic and therapeutic protocols for periodontal diseases in SLE patients by addressing underlying microcirculatory disorders.